Leadoff batters of major league baseball : complete statistics, 1900-2005 - Krabbenhoft, Herman O., 1945- (McFarland, 2006)
"From 1900 through 2004, the major leagues' leadoff batters for more than 150,000 games are covered. Discussed here are the annual records of the principal leadoff batters, the principal leadoff batter for each team in each year, statistics for those who led the roster for five or more seasons, leadoff home runs, and assorted leadoff batter achievements"--Provided by publisher